Academic management, teaching performance related to the academic performance of students enrolled - Rodas Cabanillas, José Luis (2017)
The present research work had as a general objective to determine the relation that exists between, the teaching performance, the academic management and the academic performance of the students enrolled in the courses of the highest index of disapproved in this faculty. We used a non-experimental, cross-correlational, design using a population of 1983 students extracted from 104 records that compose the courses with the highest index of disapprovals, was diagnosed with an optimal random sample of 95 students of that population, based on the proportion of students disapproved of as success, which is shown by 65% of students disapproved as an average proportion. The validation of the instruments was of constructs, using the factorial analysis with correlations of 0.60 to 0.90, the reliability of the instruments with Cronbach alpha, for the academic management was of 0.934 and for the educational performance was of 0.974. The academic performance had an average of 9,516 points, considered low according to its categorization, had a C.V equal to 31.25%, considering the average of the students of the optimum, the Spearman correlation for teaching performance and academic performance was 0.805 and that of academic management with academic achievement was 0.808, academic performance and teaching performance was 0.989. Has a model regression for those three variables, the regression model for the dimensions of teacher performance and academic performance are all significant and positive a, but the dimension at learning that do not affect academic performance significantly, the relationship of the dimensions of academic management and academic performance ,only infrastructure and service are significantly influence.